PENERAPAN MODEL PROJECT BASED LEARNING PADA MATEMATIKA KELAS IV SD XYZ KOTA DEPOK - Triani, Lia; Susianna, Nancy (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Numeracy skills, computational thinking, and collaboration need to be possessed by students to be able to adapt to advances in science, technology, and information. This study aims to analyze the differences between numeracy skills, computational thinking, and collaboration in classes that implement project-based learning and classes that apply the lecture method. This study used a weak experimental method with a static-group pretest and posttest design model. The research data was obtained through rubrics and test questions that had been tested for validity and reliability. The results of the analysis and statistical tests showed that the average value of the numeration skills rubric, computational thinking, and collaboration of students in the experimental class was greater than that of the control class. The average score of the rubric of students' numeracy skills, computational thinking and collaboration in the experimental class was 83.77; 87.17; and 90.75. While the average score of the numeration skills rubric, computational thinking and student collaboration respectively in the control class, namely 64.71; 61.76; and 77.57.